Transcriptional profiles in the mouse amygdala after a cognitive judgment bias test largely depend on the genotype - Herrera-Rivero, Marisol; Bohn, Lena; Witten, Anika; Jüngling, Kay; Kaiser, Sylvia; Richter, S. Helene; Stoll, Monika; Sachser, Norbert (Frontiers in Molecular Neuroscience, 2022)
Background: The amygdala is crucial for emotional cognitive processing. Affective or emotional states can bias cognitive processes, including attention, memory, and decision-making. This can result in optimistic or pessimistic behaviors that are partially driven by the activation of the amygdala. The resulting emotional cognitive bias is a common feature of anxiety and mood disorders, both of which are interactively influenced by genetic and environmental factors. It is also known that emotional cognitive biases can be influenced by environmental factors. However, little is known about the effects of genetics and/or gene-environment interactions on emotional cognitive biases. We investigated the effects of the genetic background and environmental enrichment on the transcriptional profiles of the mouse amygdala following a well-established cognitive bias test. Methods: Twenty-four female C57BL/6J and B6D2F1N mice were housed either in standard (control) conditions or in an enriched environment. After appropriate training, the cognitive bias test was performed on 19 mice that satisfactorily completed the training scheme to assess their responses to ambiguous cues. This allowed us to calculate an “optimism score” for each mouse. Subsequently, we dissected the anterior and posterior portions of the amygdala to perform RNA-sequencing for differential expression and other statistical analyses. Results: In general, we found only minor changes in the amygdala’s transcriptome associated with the levels of optimism in our mice. In contrast, we observed wide molecular effects of the genetic background in both housing environments. The C57BL/6J animals showed more transcriptional changes in response to enriched environments than the B6D2F1N mice. We also generally found more dysregulated genes in the posterior than in the anterior portion of the amygdala. Gene set overrepresentation analyses consistently implicated cellular metabolic responses and immune processes in the differences observed between mouse strains, while processes favoring neurogenesis and neurotransmission were implicated in the responses to environmental enrichment. In a correlation analysis, lipid metabolism in the anterior amygdala was suggested to influence the levels of optimism. Conclusions: Our observations underscore the importance of selecting appropriate animal models when performing molecular studies of affective conditions or emotional states, and suggest an important role of immune and stress responses in the genetic component of emotion regulation.